2018
DOI: 10.1111/psj.12297
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Multiple Decision Making Water Governance Forums in Brazil Enhances Actors’ Perceived Level of Influence

Abstract: The Ecology of Games Framework (EGF) draws attention to the intertwined nature of different forums in a given policy setting and how this affects governance outcomes. In this article, we associate the EGF with the literature on power asymmetries, in order to investigate hypotheses of actors’ perceived level of influence in a forum. Focusing on the Paraíba do Sul river basin committee in Brazil, we specifically explore actors’ participation in multiple forums, time spent participating in the basin committee, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…They find that actors who benefit from participation in one CGR are more likely to benefit from participation in other CGRs, which they see as an indication that participation can actually deepen existing imbalances rather than distribute benefits more equitably. These findings go in line with those reported by Mancilla García and Bodin (2018). In their study of the management of the Paraíba do Sul river, in Brazil, they show that higher levels of participation in multiple forums partially explains how actors gain influence in the governance system.…”
Section: Empirical Research On the Egtsupporting
confidence: 93%
“…They find that actors who benefit from participation in one CGR are more likely to benefit from participation in other CGRs, which they see as an indication that participation can actually deepen existing imbalances rather than distribute benefits more equitably. These findings go in line with those reported by Mancilla García and Bodin (2018). In their study of the management of the Paraíba do Sul river, in Brazil, they show that higher levels of participation in multiple forums partially explains how actors gain influence in the governance system.…”
Section: Empirical Research On the Egtsupporting
confidence: 93%
“…From this perspective, policy institutions can serve as boundary organizations, and facilitate, enable and regulate relations between internal actors. This finding is in accordance with many empirical studies using the EGF [10][11][12][13][14][15], which recognizes that policy institutions actually perform as coordinators in decision-making among multiple actors. Apart from internal actors' coordination, our empirical evidence shows positive externalities between policy institutions.…”
Section: Discussionsupporting
confidence: 91%
“…The extant studies on policy institution largely focus on the coordinative mechanisms of multiple actors within one single institution or the pattern of actor interactions within a specific regional project [5][6][7][8][9]. Only a few studies have tried to understand how different policy institutions are interlinked and mutually affected to influence policy outcomes [10][11][12]. In this article, we follow in the opinion that the policy institutions that exist at a particular time and place may generate interdependent effects and combine to define the complex institutional system of environmental governance.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from biophysical conditions, power asymmetries also affect how development programs are implemented in Tajuk. García & Bodin (2019) suggested that participation in various forums is the key to influence decision-making in water governance. Pulihan has become more robust due to several local political elites residing there.…”
Section: Inequalitiesmentioning
confidence: 99%